Modeling Vehicular CO Emissions for Time Headway-based Environmental Traffic Management System. (2015) - Elkafoury, Ahmed; Negm, Abdelazim M.; Bady, Mahmoud Farghly; Aly, Mohamed Hafez
Abstract: This paper reveals the relationship between vehicles time headway and Carbon monoxide emission factors. Traffic characteristics field measurements were conducted on road link at the entrance of New Borg El-Arab City-Egypt. Distribution of time headways for Passenger cars and Heavy vehicle were investigated. The instantaneous vehicular emission model (VT-Micro) was utilized to calculate CO emission factors of individual vehicles in different traffic situation. Real-time emission models were developed using vehicles time headway as explanatory variable. Models introduce good fit having R 2 of about 0.9 and low RMSE. Components for an intelligent traffic management system (ITMS) for controlling emissions were proposed.